Preoperative Progressive Pneumoperitoneum and Botulinum Toxin Type A in Patients With Large Parastomal Hernia - Tang, Fu-Xin; Ma, Ning; Xie, Xing-Xing; Chen, Shuang; Zong, Zhen; Zhou, Tai-Cheng (Frontiers in Surgery, 2021)
Background: The combination of preoperative progressive pneumoperitoneum (PPP) and botulinum toxin type A (BTA) in adjuvant treatment of large parastomal hernia (LPH) has not been reported in the previous literature. Methods: From February 2018 to June 2019, 16 patients were diagnosed with LPH in our hospital were included in this study. All patients received PPP and BTA treatment to expand abdominal volume and extend abdominal muscle before surgery. The laparoscopic Sugarbaker method was preferred for defect close. Results: Before and after PPP and BTA, the mean volume of the parastomal hernia (VPH) was 1,522 and 1,644 cc, respectively (P < 0.01), and the mean volume of the abdominal cavity (VAC) was 5,847 and 9,408 cc, respectively (P < 0.01). The VPH/VAC ratio was decreased by an average of 8.4% after the combination management. And the lateral abdominal muscle length was increased by an average of 4.8 cm/side (P < 0.01). These patients underwent surgery successfully, and no hernia recurrence after (17.6 ± 2.4) months of follow-up. Conclusions: The combination of PPP and BTA effectively expand the abdominal volume, decrease the risk of abdominal compartment syndrome (ACS) postoperatively, and beneficial to laparoscopic repair of LPH.